Peer effects, gender, and intellectual performance among students at a highly selective college : a social comparison of abilities analysis - George R. Goethals (Williams College, Williams Project on the Economics of Higher Education (WPEHE), 2001)
A study was conducted to examine peer effects among undergraduates at Williams College, a highly selective four-year liberal arts school. Specifically, the study explored whether students would perform better writing about newspaper articles they read and discussed in academically homogeneous or heterogeneous groups of three. In homogeneous groups all three students were from either the top half or bottom half of their class on academic ratings assigned at the time of admission. Heterogeneous groups included students from both the top and bottom half of their class. The results showed that students in the top and bottom half performed similarly overall, but that students performed better in homogeneous groups, whether those homogeneous groups were made up of students in the top half or the bottom half of their classes. This pattern of results was stronger for men subjects than women subjects. The results were interpreted in terms of the principles of social comparison theory (Festinger, 1954).
Keywords: 330; Bildungsverhalten; Studium; Geschlecht; USA; peer effects